Budidaya dan Produktivitas Kopi di PT. Perusahaan Perkebunan Kandangan Pulusari/Panggungsari, Madiun - Junun Sartohadi (Pancasila bureaucracy, Journal of Regional Government, Development and Innovation, 2023)
This study aims to determine the cultivation and productivity of coffee at PT. Plantation CompanyKandangan Pulusari/ Panggungsari, Madiun. Data analysis in this study used documentationtechniques. Data analysis is carried out by data reduction, data presentation, and conclusions.Based on the results of the study, it is known that technical cultivation, social aspects, and legalitywhich are all three interrelated are problems that occur in the company. There is a change inownership of PT. The Kandangan Pulusari/Panggungsari Plantation Company greatly impactedthe company's management, until in the end there was no maintenance and many shade plantswere cut down. The lack of labor that is not proportional to the area of the garden may be one ofthe foundations of poorly maintained gardens and cause less than optimal cultivation. The issueof land with the status of Right to Use (HGU) which has expired its permit in 2012, createsconflicts with the community. The community began to utilize plantation land by plantingcommodities other than coffee, namely food commodities, and crops. In addition, irregular andappropriate spacing between coffee plants and shade plants causes the quality of the coffee beansproduced cannot be maintained properly.